Perception of Adolescents About Intrusive Advertising at Telkomsel Providers and XL Axiata - Yoga Dwi Ramadika; Puji Lestari; Isbandi Sutrisno (Jurnal Ilmu Komunikasi, 2019)
This research aims to find out the perception and decision-making of consumers related to intrusive advertising in Telkomsel and XL Axiata providers among Yogyakarta teenagers. This research uses qualitative descriptive methods by conducting observations, in-depth interviews with Telkomsel and XL Axiata provider users, and documentation of examples of intrusive advertising. The results of this study found that the perception of provider users could be positive and negative perceptions of intrusive advertising. Provider user perception is divided into three categories: The first category is the provider user who does not care about intrusive advertising. The second is the user of the provider who is disturbed by the intrusive advertising and continues to use the provider. Third, the user of the provider who is very disturbed by the intrusive advertising and replaces the provider with another. These perceptions can influence decision-making to use the provider. This research contributes in the form of advice to providers to follow the ethics of Indonesian advertising so as not to interfere with the convenience of users while browsing.